PEMANFAATAN BIOPORI DALAM PENGELOLAAN SAMPAH ORGANIK SEBAGAI UPAYA PENCEGAHAN MITIGASI BERKELANJUTAN - Pariyatin, Yeni; Muthmainah, Nisrina; Nur’aini, Alifia Munira; Apriadi, Ruby Ardha; Dimukti, Candra Setia; Pratama, Ari; Gustopa, Rega; Ramadhan, Ilham Salman; Husein, Hasyir Ahmad; Ramdani, Rendi; Fauzi, Muhammad Fadil; Khopi, Dzikri; Fadia, Agna; Maulina, Regista Ristia; Fajri, Fadhlian Nur; Sopian, Muhamad Jafar; Albari, Rabiul Tsani Ghifarulhaq; Widad, Rafi Nur; Hijazi, Mochamad Inda; Wulandari, Dedeh; Maulana, Hendi Rivana; Permana, Aditya; Latifa, Aulia (Institut Teknologi Garut, 2025)
One of the main challenges in environmental governance in rural areas today is the management of organic waste. In Garut Regency, Cipaganti Village, located in Cisurupan District, produces a significant amount of organic waste from household and agricultural activities. When not properly managed, accumulated organic waste can pollute the environment, cause foul odors, and become a source of disease. To address this issue, the biopore infiltration technique was introduced as an environmentally friendly method that not only enhances water absorption but also supports waste reduction. This study aims to utilize biopores in organic waste management as a sustainable mitigation effort in Cipaganti Village, Cisurupan District, Garut Regency. The research employed a participatory approach involving village officials, community groups (RISMET), and local residents. Activities included coordination, field observation, community outreach and education, direct implementation of biopores, as well as monitoring and evaluation. The results indicate that biopores are effective in reducing household organic waste, improving soil water absorption, and producing compost beneficial for local agriculture. The program was well received by the community due to its simplicity, low cost, and ease of implementation. Therefore, the use of biopores in Cipaganti Village has the potential to become a sustainable solution for organic waste management, water conservation, and raising public awareness about the importance of maintaining environmental cleanliness.